ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KONSUMEN DI E-COMMERCE : STUDI LITERARUR REVIEW - Shelvy Shaylina; Nur Anisa; Dwi Astuti (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The advancement of information technology is marked by remarkable developments. The need for information technology in human existence is becoming increasingly important. The essential function of information systems technology is to facilitate or enhance the effectiveness and efficiency of human labor. This advancement in information technology has a significant impact on all dimensions, particularly on the evolution of the business and marketing sectors. This phenomenon is not surprising, considering the continuously increasing number of Internet users represents a potential market for entrepreneurs. Conversely, e-commerce and e-business practices offer numerous advantages for both companies and consumers.This research aims to determine the factors influencing consumer purchasing decisions in online stores, with data obtained from relevant literature from 2016 to 2024. The method used in this study is the Systematic Literature Review (SLR). The SLR method is employed to identify, review, evaluate, and interpret all available research in the subject area of the intriguing phenomenon, as well as specific related research questions. By using the SLR method, journal articles can be systematically reviewed and identified, and the predetermined steps or procedures can be followed in each process.The research findings highlight that trust and promotion have a significant impact on purchasing decisions. This study provides guidance for the development strategies of e-commerce businesses in Indonesia.